To Study the Epizootological Status of Trichophytia in Cattle Breeding in the Conditions of Uzbekistan - Zhurraevna, Usmonova Khadicha (European Journal of Life Safety and Stability (2660-9630), 2021)
This article examines the epizootiology of trichophytes occurring in the cattle population, depending on the season of the year. Lighting in the context of the breeding seasons of the fungus trichophytes of cattle during the study.